La diagnosi psichiatrica e i diritti umani - Dell’Erba, Alice (Il sogno della farfalla, 2016)
In the twenty years that followed World War II, we saw the disappearance of classic psychiatric taxonomy which had lead to the classification of the main psychiatric syndromes. In the USA, due to the spreading of psychoanalysis and of psycho-social model, and to the publication of DSM, the word “disease” disappeared to be replaced by the word “disorder”. This lead to the progressive impoverishment of research on mental diseases, which have been reduced to a list of symptoms that are statistically linked to one another. In Europe, the existence of mental disease itself was questioned due to a dangerous mix between psychiatry and Existentialism. In order to overcome this impasse, the author suggests taxonomic research up to Bleuler be resumed and reviewed in the light of new findings on human birth.